Corona’s Reflections on Contemporary Arabic Poetry (Corona Pandemic Poem by Hashem Al-Bashir As a model) - Salih, Salih Shuaib; Ismail, Maha Ahmed (Arab Journal for Sciences and Research Publishing, 2020)
This research aimed to clarify the reflections of Corona on contemporary Arabic poetry, and to explain the extensions of pandemic literature in the imaginations of contemporary poets, and to emphasize that contemporary Arab poetry A smooth surface from which the events and developments of life are reflected, and the researcher chose the poem of the Sudanese poet Hashem Al-Bashir, which he called (Corona Pandemic) as a model through which he shows the interaction of contemporary Arabic poetry with his reality, his portrayal of what is happening in his society, and his expression of what is happening in his world, with printed poetry and a delicate feeling, And rhetorical aesthetics apparent, and the researcher followed the descriptive analytical approach. The results were reached, the most prominent of which is that the poet Hashem Al-Bashir was able to depict the impact of the Corona pandemic on all aspects of social, economic, political and cultural life, and he expressed the variables that swept the world due to the pandemic, and narrated what happened to countries and cities as a result of that real disaster, and that was in a sober and sober manner, Sweet rhythm, smooth phrases, sincere feeling, beautiful expressions, reflects a high culture and multiple talents, crystallized by his poetics, whose words produced balanced rhythms from the poet’s heart, flowing to the ears, touching hearts.